Penyiangan dan Pemangkasan Cabang Tanaman Tomat (Lycopersicon esculentum Mill.) terhadap Keragaman dan Kepadatan Gulma: Weeding and Pruning of Tomato (Lycopersicon esculentum Mill.) on Weed Diversity and Density - Nur Hidayat; Jody Moenandir (Agrocentrum, 2023)
A field experiment to examine the effect of weeding and reducing the number of branches on tomato plants (Lycopersicon esculentum Mill.) on weed diversity and density was carried out in the Griya Santa research area, Lowokwaru District, Malang City with andosol soil type. This experiment was designed in a factorial randomized block design (RBD) with 2 factors and 3 replications. The first factor is: the weeding period (P) which consists of 3 weeding periods, i.e. without weeding (P0), 2 times weeding at 30 and 58 days after planting (P1) and 3 times weeding at 30, 44 and 58 days after planting (P2). The second factor was: pruning the number of tomato plant branches (W) which consisted of 3 levels, namely: Without pruning branches (W0), Pruning branches leaving 2 branches (W1) and Pruning branches leaving 4 branches (W2). All treatment plots were repeated 3 times. The experimental results showed that at 30 DAP (P0W0) there were 2 dominant weeds namely Portulaca oleraceae and Cyperus rotundus. At 44 DAP it showed that there were also 2 dominant weeds namely: Ricinus communis and Cyperus rotundus. The most dominant P2W0 weed treatments were Ricinus communis and Ageratum conyzoides. The P0W1, P1W1, P0W2, and P1W2 treatments had weed species: Ricinus communis and Cyperus rotundus. The dominant weeds found in the P2W1 and P2W2 treatments were Ricinus communis and Portulaca oleraceae.